SINERGI PERSONAL BRANDING CEO DAN CONTENT MARKETING DALAM STRATEGI TECHNOPRENEURSHIP KLINIK & APOTEK MAS BANJARBARU - Martin Agusta; Eddy Soeryanto Soeogoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
This study aims to analyze the synergy between CEO personal branding and content marketing within the technopreneurship strategy implemented at MAS Clinic and Pharmacy, Banjarbaru, South Kalimantan. A descriptive qualitative approach was employed through digital observation of the official Instagram account, social media content analysis, and examination of digital technologies supporting healthcare services and marketing. The findings reveal that digital transformation extends beyond service digitalization by strengthening health education, communication, and marketing through social media. Educational content featuring doctors and healthcare professionals increases audience engagement, fosters emotional connection, and enhances brand awareness and public trust. The main finding demonstrates that the synergy between CEO personal branding and institutional content marketing organically expands market reach, improves marketing cost efficiency, and strengthens the competitiveness of healthcare services. Furthermore, this strategy supports all stages of digital consumer behavior based on the Attention, Interest, Search, Action, and Share (AISAS) model. The study concludes that integrating digital leadership with educational content marketing represents an effective technopreneurship strategy for enhancing public trust while reinforcing the competitive position of healthcare providers within the digital healthcare ecosystem.